Characterization on the toxic mechanism of two fluoroquinolones to trypsin by spectroscopic and computational methods. Issue 3 (3rd March 2020) - Guo, Yanxiu; Qin, Pengfei; Wang, Chaoyun; Pan, Xingren; Dong, Xiaofei; Zong, Wansong
Abstract: Ciprofloxacin (CPFX) and enrofloxacin (ENFX), two of the most widely used fluoroquinolones (FQs), pose a great threat to humans and the ecosystem. In this study, the toxic mechanisms between the two FQs and trypsin were evaluated by means of multiple spectroscopic methods, as well as molecular docking. During the fluorescence investigations, both FQs quenched the intrinsic fluorescence of trypsin effectively, which was due to the formation of moderately strong complexes (mainly through van der Waals forces and hydrogen bonds). The binding of two FQs not only caused the conformational and micro-environmental changes of trypsin, but also changed its molecular activity; shown by the UV–Visible absorption spectroscopy, synchronous fluorescence spectroscopy, and functional tests. The established methods in this work can help to comprehensively understand the transport of FQs in the human body.